1990
DOI: 10.1002/cne.902980104
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid projections to the frontal cortex and the striatum in the rat

Abstract: Projections from the basolateral nucleus of the amygdala (BLA) to the frontal cortex and the striatum were studied by using Phaseolus vulgaris-leucoagglutinin (PHA-L) anterograde tracing technique in the rat. PHA-L injections into the rostral part of the BLA resulted in a dense labeling of fibers with boutons in the dorsal bank of the rhinal fissure and in the lateral and the medial agranular cortex. PHA-L injections into the caudal part of the BLA produced a dense labeling of fibers in the medial surface of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
222
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(239 citation statements)
references
References 36 publications
14
222
3
Order By: Relevance
“…Indeed, it was found that muscarinic receptor blockade interferes with the stabilizing and facilitating effects of BLA stimulation on LTP of thalamocortical (24) and perforant path (23) synapses. However, because the cholinergic innervation of the striatum mostly has an intrinsic origin (49) and BLA axons do not target striatal cholinergic interneurons (34), such a mechanism is unlikely to explain our results. Together, these data suggest that BLA axons may influence synaptic plasticity through several parallel mechanisms.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Indeed, it was found that muscarinic receptor blockade interferes with the stabilizing and facilitating effects of BLA stimulation on LTP of thalamocortical (24) and perforant path (23) synapses. However, because the cholinergic innervation of the striatum mostly has an intrinsic origin (49) and BLA axons do not target striatal cholinergic interneurons (34), such a mechanism is unlikely to explain our results. Together, these data suggest that BLA axons may influence synaptic plasticity through several parallel mechanisms.…”
Section: Discussionmentioning
confidence: 81%
“…Only monosynaptic responses were included in the analysis, and the initial half of the rising phase was analyzed for changes in slope. Because BLA and cortical projections are believe to arise from glutamatergic neurons (34,35), it is highly unlikely that the early part of the responses evoked by BLA and cortical stimuli were reversed inhibitory postsynaptic potentials (IPSPs). Moreover, the striatum does not project back to the cortex or amygdala.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the NAcc and related neural pathways are involved in the psychostimulant effects of amphetamine (Wolf, 1998;Rockhold et al, 1998;Wolf et al, 2004;Kalivas and Volkow, 2005). Neuroanatomical studies have indicated that DA neurons in the NAcc receive significant glutamatergic input directly from the limbic cortex and sub-cortical structures (Groenewegen et al 1980;Kelley and Domesick 1982;Kita and Kitai 1990;Parent and Hazrati, 1995;Sesack et al, 1989;Tzschentke and Schmidt, 2000). Since activation of direct and indirect glutamate pathways increases glutamate release in NAcc following acute amphetamine injection (Robinson and Beart, 1988;Parent and Hazrati, 1995;McGinty, 1999;Vanderschuren and Kalivas, 2000), a potential role for glutamate-mediated mechanisms is implicated in the environment-dependent alteration in amphetamine-induced effects in NAcc.…”
Section: Discussionmentioning
confidence: 99%
“…The area of interest encompassed the dorsal edge of the rhinal sulcus, which connects to the BLA (Kita & Kitai, 1990). The majority of lesions in the cortex (73%) included complete tissue loss (neurons, fibers, and neuropil) and resulted in glial cells sealing off the damaged region.…”
Section: Ofc Lesioningmentioning
confidence: 99%